Hear #metoo in India : news, social media, and anti-rape and sexual harassment activism - Guha, Pallavi (New Brunswick, New Jersey : Rutgers University Press, 2021)
This book examines the role media platforms play in anti-rape and sexual harassment activism in India. Including 75 interviews with feminist activists and journalists working across India, it proposes a framework of agenda-building and establishes a theoretical framework to examine media coverage of issues in the digitally emerging Global South.
Cover -- Title Page -- Copyright -- Dedication -- Epigraph -- Contents -- 1. Introduction and Historical Background -- 2. Framing of Rape in the News Media and Its Impact on Feminist Activism and Journalists: #MeTooIndia Including Themes -- 3. The Heart Does Not Bleed for Everyone: Selective Outrage and Activism -- 4. The Successes and Failures of Transnational Hashtag Movements -- 5. Moving Forward: Learning from Anti-rape Feminist Movements -- Acknowledgments -- Notes -- References -- Index -- About the Author
eBooks on EBSCOhost
Keywords: Rape victims -- India; Sexual harrassment -- India; Sexual abuse victims -- India; Women -- Violence against -- India; Women -- Political activity -- India; Feminism -- India; Victimes de viol -- Inde; Victimes d'abus sexuels -- Inde; Femmes -- Violence envers -- Inde; Femmes -- Activité politique -- Inde; Féminisme -- Inde; SOCIAL SCIENCE / General; Feminism; Rape victims; Sexual abuse victims; Women -- Political activity; Women -- Violence against; India; #metoo, India, Anti-rape, Rape culture, Sexual Harassment, Feminism, Activism, Global South, Time magazine, #metoo movement, social media, mainstream, mass media, Cultural Studies, Media, Journalists, Public Policy, Urban Region, Rural Region